PENENTUAN MATRIKS KESELAMATAN BERLAYAR KAPAL PERIKANAN TERHADAP TINGGI GELOMBANG DI PERAIRAN SELAT MAKASSAR SULAWESI SELATAN - Anendha Destantyo Nugroho; Ihsan Ihsan; Asbar Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The purpose of this study was to determine the characteristics of significant sea waves and seasonal wind in the west season, west to east transition season, east season and east to west transition season and determine the sailing safety matrix of fishing vessels against high waves in the Makassar Strait Waters. The method in this study is the Observation Method by conducting interviews with the help of questionnaires with 30 fishermen respondents who own boats at the Untia Fisheries Port which are samples. The results obtained during the west season significant wave height in Makassar Strait Waters ranged from 0.5 - 1.0 meters, and the wind blew from the southwest to the northwest at a speed of 2 - 15 knots, during the west to east transition season significant wave height in Makassar Strait Waters ranged from 0.5 - 1.0 meters, and the wind blew from the northeast to southeast at a speed of 8 - 15 knots, during the east season significant wave heights in Makassar Strait Waters range from 0.75 - 1.5 meters, and the wind blows from the east to the southeast at a speed of 10 - 20 knots while during the east to west transition season significant wave heights in Makassar Strait Waters range from 0.75 - 1.25 meters, and the wind blows from the east to the southeast at a speed of 8 - 15 knots. Based on the results of processed wave data and wind patterns, the safety matrix for sailing fishing vessels is obtained, for small vessels 1 - 10 GT is safe to sail on low category waves, medium size vessels 11 - 20 GT is safe to sail on medium category waves and for large size vessels 21 - 30 GT is still safe to sail on high category waves.